2018
DOI: 10.1371/journal.pone.0201077
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical therapies to prevent or treat fracture non-union: A systematic review

Abstract: BackgroundNon-union affects up to 10% of fractures and is associated with substantial morbidity. There is currently no single effective therapy for the treatment or prevention of non-union. Potential treatments are currently selected for clinical trials based on results from limited animal studies, with no attempt to compare results between therapies to determine which have the greatest potential to treat non-union.AimThe aim of this systematic review was to define the range of therapies under investigation at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…Although no human trials have yet to evaluate chitosan as a treatment modality for non-union, a number of animal studies have utilised chitosan either alone or in conjunction with another therapy in models of non-union. A recent systematic review examining pre-clinical therapies to prevent or treat non-union identified chitosan as a promising osteogenic agent 74 . Four out of six papers that utilised chitosan as a treatment for an animal model of non-union found that chitosan was superior to a control treatment 75-78 .…”
Section: Future Research Foci and Needsmentioning
confidence: 99%
“…Although no human trials have yet to evaluate chitosan as a treatment modality for non-union, a number of animal studies have utilised chitosan either alone or in conjunction with another therapy in models of non-union. A recent systematic review examining pre-clinical therapies to prevent or treat non-union identified chitosan as a promising osteogenic agent 74 . Four out of six papers that utilised chitosan as a treatment for an animal model of non-union found that chitosan was superior to a control treatment 75-78 .…”
Section: Future Research Foci and Needsmentioning
confidence: 99%
“…Protected by copyright. 15 This systematic review seeks to identify whether the ability of the military surgeon to achieve union in fractures sustained in the combat environment has improved over a century of conflict.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies discovered the overall relative risk of non-union in long bone fracture to range from 1.9-10%, with observable peaks in young adults. 1,2 Inadequate care of several factors may contribute to the diminution of bone healing, which includes mechanical, biological, and infection. 3,4 Among these, an infection may be present in up to 40% of non-union cases.…”
Section: Introductionmentioning
confidence: 99%
“…However, outcomes from this procedure vary widely and can lead to a series of revision surgeries. 2 Different bone grafts are used in cases where defects are present; these can range from autograft, allograft, or synthetics grafts. After ten years, graft failure is still observed in approximately 60% of cases, leading to recurring non-union.…”
Section: Introductionmentioning
confidence: 99%